Investigation of Ultra-and Nanofiltration for Separation of Proteins and Lactose from Dairy Wastewater - Zhang, Yongfeng; Bai, Jie; Zhang, Jianbin; Wang, Xiaoyan; Cui, Jingdong (Asian Journal of Chemistry, 2012)
In this study, the proteins and lactose were separated from dairy wastewater using ultrafiltration. The effect of transmembrane pressure, feed flowrate, concentration factor on the recycle results are studied systematically. The permeate flux, protein and lactose content in the permeation and in the concentrate fractions were measured during the experimental runs. Meanwhile, the removal efficiency of COD is checked. It was found that ultrafiltration membrane provided 94-97 % recovery of protein in dairy wastewater and nanofiltration membrane provided 100 % recovery of lactose in ultrafiltration permeate. An increase in transmembrane pressure (TMP) increased the permeate flux which increased the rate of protein and lactose being recovered. The nanofiltration membrane showed approximately 96-99 % rejection of COD, the percentage being low at lower transmembrane pressures (greater than 10 bar) and high and higher transmembrane pressures (less than 10 bar). The nanofiltration permeate could be up to the standard of reusable water.